Analysis of the Initial Imperfections Effect on the Thin-Walled Cold-Formed Compressed Steel Members - Ali, Mohamad Al; Tomko, Michal; Demjan, Ivo; Kvocak, Vincent (Communications - Scientific letters of the University of Zilina, 2012)
The paper deals with the influence of initial imperfections and presents fundamental information about experimental and theoretical-numerical research to determinate the load-carrying capacity of thin-walled cold-formed compressed steel members. The investigated members had closed cross-sections made of homogeneous material. The theoretical-numerical analysis in this paper is oriented on the investigation and modeling of initial imperfections effects, caused by production process, on the load-carrying capacities of mentioned members, while the experimental investigation is to verify the theoretical results and to investigate the behavior of mentioned members during the loading process.